Third-Generation Tyrosine Kinase Inhibitors Targeting Epidermal Growth Factor Receptor Mutations in Non-Small Cell Lung Cancer - Barnes, Tristan A.; O’Kane, Grainne M.; Vincent, Mark David; Leighl, Natasha B. (Frontiers in Oncology, 2017)
Sensitizing mutations in the epidermal growth factor receptor (EGFR) predict response to EGFR tyrosine kinase inhibitors (TKIs) and both first and second generation TKIs are available as first line treatment options in patients with advanced EGFR mutant non-small cell lung cancer (NSCLC). Eventual resistance develops with multiple mechanisms identifiable both upon repeat biopsy and in plasma circulating tumor DNA (ctDNA). The T790M gatekeeper mutation is responsible for almost 60% of cases. A number of third generation TKIs are in clinical development, and osimertinib has been approved by the FDA for the treatment of patients with EGFR T790M mutant lung cancer after failure of initial EGFR kinase therapy. Resistance mechanisms are being identified to these novel agents, and the treatment landscape of EGFR mutant lung cancer continues to evolve. The sequence of EGFR TKIs may change in the future and combination therapies targeting resistance appear highly promising.